A standardized monitor for the control of ethylene oxide sterilization cycles. - Dadd, A. H. (Cambridge University Press, 1983)
The resistance of spores of B. subtilis var. niger produced in liquid synthetic medium and exposed to ethylene oxide on a nylon surface, has been shown to the almost identical to that for spores produced on a traditional solidified complex medium with exposure to the sterilant on aluminium foil. The use of short lengths of nylon tube as carriers allowed easy production and handling, with self-protection of the spore-bearing surface. Addition of a dye provided visual evidence of inoculation without affecting resistance to ethylene oxide. Such a monitor is suitable for use as a standardized biological challenge in routine ethylene oxide sterilization cycles.